Transforming volleyball passing technique learning through the stad cooperative model - Ayu Oktolita Pertiwi; Mashud Mashud (Sriwijaya Journal of Sport, 2025)
Research Problems: At Madrasah Aliyah 2 in Banjarmasin City, many students still have difficulty mastering the basic technique of underhand passing, namely a lack of understanding of the concept of underhand passing, conventional teaching methods, and a lack of active student involvement in learning. Research Objective: The objective of this study is to improve underhand passing in volleyball through the STAD Cooperative Model. Method: This study is a Classroom Action Research based on the Kemmis and McTaggart cycle, which includes planning, implementing actions, observation, and reflection. The research subjects were 34 students from class X of MAN 2 Banjarmasin, and the research instruments were observation sheets for underhand passing skills and cognitive ability tests. Results: In Cycle I, 18 students (53%) mastered the underhand pass, and 20 students (58.82%) mastered volleyball knowledge. In Cycle II, there was an improvement, with 28 students (82.35%) mastering the underhand pass technique and 30 students (88.23%) mastering volleyball knowledge. Conclusion: The STAD cooperative learning model has proven effective in improving students' learning outcomes in cognitive and psychomotor aspects in the teaching of underhand passing techniques in volleyball.